Microwave antenna/filter synthesis and optimization - Ng, Jin Kai (2019)
Microstrip discontinuities like open ends, right-angle bend and T-junctions are crucial in understanding the basic microstrip designs. In this Thesis, we study the S-parameters and carry out fast approximate modeling for microstrip discontinuities to model wire-grid microstrip antennas and develop a methodology for future researchers to aid in other complex microstrip designs.